Violação à razoável duração do processo e à demarcação das terras indígenas: uma análise do acesso à justiça à luz da Convenção Americana de Direitos Humanos - Cordeiro, Iasmim Madeiro (2021)
The Brazilian Federal Constitution of 1988, in Article 5, subsection LXXVIII, establishes the reasonable duration of the process and the means to ensure that it is carried out quickly, which is in line with the American Convention on Human Rights in Articles 8 and 25, both of which guarantee access to justice. Here, it is of interest to analyze how the aforementioned norms are applied and put into effect when the indigenous peoples are the target group. Thus, the objective of the present work is to verify which conditions made a faster demarcation process impossible, based on the analysis of the administrative process of demarcation of the indigenous land of the Xukuru people nº 08620.000052/1990-76, located in Pesqueira - PE. The problem discussed here is verified in the contraposition between what is positived in the national and international legal mechanisms mentioned above and what is visualized in practical reality, such as the excessive delay for demarcation of indigenous territory. The constant violation of the rights and maintenance of indigenous peoples as extremely vulnerable and subaltern prints the colonial idea of being, knowledge and power, visualized in the power relations that repeatedly treat such peoples as inferior. Thus, it seeks to analyze the right to the reasonable duration of the process as a fundamental human right from an intercultural perspective, to deepen the study on the demarcation of indigenous lands and the case of the Xukuru people, and finally to verify which categories have caused a lengthy procedure. This research is important and of considerable social relevance because it deals with the violation of fundamental human rights by analyzing the process of a people who are part of minorities in a state of vulnerability. The hypothesis is that there are barriers that prevent the demarcation process from being reasonably long, making it too extensive and consequently violating so many other rights of the people it seeks to protect. The intention is to carry out a case study of a descriptive-exploratory type, of a qualitative nature and using the research technique of content analysis.